The velocity structure of the volcanic plumbing system of Gede Volcano, West Java, Indonesia - Hidayat, Dannie (2023)
We estimated the velocity structure beneath four three-component broad-band seismic stations and three short period stations in the Gede Volcano region, West Java, Indonesia by the receiver function (RF) technique jointly with H/V (Horizontal/Vertical) amplitude ratio of Rayleigh waves to constrain the 1D velocity structure around each station, and in the back-azimuth of the source considered, ultimately providing a 3D understanding of the velocity structure of the volcanic plumbing system. The stations are part of the collaborative seismological network between Center for Volcanology and Geological Hazard Mitigation (CVGHM) and Earth Observatory of Singapore (EOS). Our preliminary result suggest the depth of the Moho is about 30 km. Based on the back azimuth of the earthquakes, the receiver functions inversion and H/V amplitude radio from the earthquakes coming from the NE-SE direction exhibit strong negative signals between direct P and Pms phase correspond to a low velocity layer in the crust, predominating all broadband station stations. This is consistent with the result of previous study of travel time tomography. We observed very few earthquakes from SW-NW direction where the receiver functions show differently from the first group due to the waves travel to magmatic body. Combining results from this study and the tomography we aim is to further find the magmatic body under the volcano at shallow as well as deeper depths. Since we have 10-year data, we will be able to see the yearly evolution or changes of the magmatic system under the volcano.